Between Philology and Radical Enlightenment : Hermann Samuel Reimarus (1694-1768). - Mulsow, Martin (Brill's studies in intellectual history, 2011)
Drawing on new manuscript sources, this volume offers seven contributions on Hermann Samuel Reimarus, the most significant biblical critic in eighteenth-century Germany, as well as an eminent Enlightenment philosopher, a renowned classicist, and expert on Judaism.